Fitotoxicidade de herbicidas em função do manejo do nitrogênio no milho - Endrigo, Paulo Cesar (2015)
The maize cycle (Zea mays) has stages of development in which it seeks to maintain its sanity and adequate nutritional demand. However, due to the rapid development of the crop, the management stages occur in a short period of time, which often coincide with the simultaneous application of herbicides and fertilizers. The objective of this research was to evaluate the interaction of post-emergent herbicides, seasons and methods of application of nitrogen fertilization to cover corn phytotoxicity and grain yield. Two experiments were installed in the field in the years of 2012 and 2013 and in greenhouse in the year 2014 (Experiment I and II). The experimental design was randomized blocks, arranged in sub-subdivide (field) and sub-divided plots (greenhouse), with four replications. In the field experiment, the main plot consisted of herbicides (nicosulfuron, mesotrione and tembotrione) and control (glyphosate), the subplots consisted of nitrogen (N) management times (7 days before herbicide application Day of application of the herbicides - ND and 7 days after the application of the herbicides 7 7 DD) and in the sub-subplots the nitrogen (N) management method (soil incorporated or distributed under cover) was evaluated. In the Greenhouse experiment the same herbicides and application times of N were used in Experiment I and in Experiment II the hybrid P1630H was added. The analyzes of the response variables indicated phytotoxicity reduction with the development of the crop, independently of treatments, becoming non-existent at 21 days after application of herbicides (DAH). The effects of treatments on total photosynthesis started at 14 DAH. The grain weight per spike and dry matter (DM) of the aerial part in the V8 stage increased when nitrogen (N) was applied at 7 DD. The plant height was lower due to the use of mesotrione and the greater spike insertion when the application time of N was performed 7 DD. Grain yield was not affected by herbicides and method of application of N and increased when the time of application of N was performed at 7 DD. N uptake reduced herbicide phytotoxicity when compared to the haul method. In a greenhouse, the symptoms of phytotoxicity reduced with the development of the crop. The shoot MS in V8 reduced as a function of mesotrione and nicosulfuron and increased when the N application time was performed ND, but did not differentiate from the application at 7 DD. The shoot MS in V8 increased for the P30F53HR hybrid over P1630H. The relative chlorophyll content decreased as a function of the herbicides and total photosynthesis (FT) increased for the hybrid P1630H from 14 DAH. Quantum photosynthesis (QY) increased for the hybrid P30F53HR at 14 DAH. The chlorophyllometer and fluorometer used as parameters to confirm leaf damage caused by herbicides and to measure the photosynthetic efficiency of the plants. The greenhouse results confirmed the field results, since the crop presented, in both situations, potential for recovery after foliar damage caused by herbicides.